Mengembangkan Kemampuan Membaca Al-Qur’an Pada Anak Usia 5-6 Tahun Di PG/RA Avesiena Sarirogo Sidoarjo Melalui Media Kartu Huruf Hijaiyah - Asmaul Husnah; Novita Widyaningrum (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
This study aims to develop the ability to read the Qur'an in children aged 5-6 years in PG / RA Avesiena through the medium of hijaiyah letter cards, against the background of low reading of the Qur'an. This research uses a qualitative approach with a case study strategy. Research site inPG/RA Avesiena Sarirogo Sidoarjo. In children aged 5-6 years. Subjects of study; Children, Principals, Teachers, and Parents. The data collection of this study by means of; observation, interviews, documentation, and questionnaires. After the data is collected, data analysis is carried out by presenting data, and drawing conclusions. The formulation of the problem in this study is: 1) How to develop the ability to readthe Qur'an in children aged 5-6 years in PG / RA Avesiena Sarirogo Sidoarjo through the medium of hijaiyah letter cards?, 2) How is the ability to read the Qur'an for children aged 5-6 years in PG / RA Avesiena Sarirogo Sidoarjo afterusing hijaiyah letter card media? The results of the study: how to develop the ability to read the Qur'an in PG / RA avesiena, namely by using the media of hijaiyah letter cards and to improve the ability to read the Qur'an for children aged 5-6 years, it is stated that it has shown proven success from the improvement of the ability to read the Qur'an.